Precarity and Resistance: A Critique of Martha Fineman's Vulnerability Theory. (2021) - Davis, Benjamin P.; Aldieri, Eric
Abstract: Contemporary feminist theory by and large agrees on criticizing the traditional, autonomous subject and instead maintains a relational, dependent self, but the vocabulary used to describe the latter remains contested. These contestations are seen in comparing the approach of some feminist legal theory, as demonstrated by Martha Fineman, to the approach of some feminist theory that draws on continental philosophy, as demonstrated by Judith Butler. Fineman's concept of vulnerability emphasizes the universality of vulnerability in the human condition, arguing that a "responsive state" is most conducive to producing subjects who are "resilient" in the face of neoliberal pressures. We argue that vulnerability, as an existential as opposed to a political description, is a limited rubric under which to organize against neoliberal forces. Further, we contend that Fineman's rhetoric of resilience risks reiterating a neoliberal logic of individualized self-management. In response, we look to Butler's concept of precarity, which underscores particular social conditions, as opposed to universal ontological vulnerabilities, that debilitate certain subjects. At stake is how we respond to neoliberal forces today: a vocabulary of precarity poses a more effective challenge than one of vulnerability, for it opens onto not merely individual or institutional resilience but grounded, communal resistance.